Dibenzazepinyl ureas as dual NMR and CD probes of helical screw-sense preference in conformationally equilibrating dynamic foldamers. Issue 78 (6th September 2017) - Diemer, Vincent; Maury, Julien; Le Bailly, Bryden A. F.; Webb, Simon J.; Clayden, Jonathan
Abstract : Dibenzazepinyl ureas act as probes to allow conformational analysis of screw-sense preference in dynamic foldamers by both NMR and CD spectroscopy. Abstract : Conformationally mobile oligomers with helical structures, or 'dynamic foldamers', may populate a mixture of screw-sense conformers whose relative proportion has been used as a means of communicating information on a molecular scale. The dibenzazepinyl urea provides a means of quantifying both the sense and degree of this screw-sense preference through a combination of circular dichroism (CD) and NMR spectroscopy. The dibenzazepinyl urea probe is synthetically versatile, readily accessible, and easy to introduce to the terminus of an amide or a urea foldamer.